Odpowiedzi

2010-02-07T15:52:30+01:00

a) x=14 - 2
x=12
b) y=48/ :4
y=12
c) (7x=24 -3) / :7
x=3
d) 7w -2w = 5/ :5
w=1
e) 10z - 5z =20 - 5/ :5
5z=15/ :5
z=3
f) 24u - 20 u=23 - 7 u /:4
4u=16/:4
u=4
g) (9x - 6x=2 - 1) /:3
3x=1
x=0.3(3)
h) 15k - 11k=8 - 67
4k=-59/:4
k= -14.75

2010-02-07T15:56:04+01:00

Niewiadome przynosimy na lewo,a wiadome na prawo

a) x+2=14
x=14-2
x=12
b) 4y=48/:4
y=12
c) 7x+3=24
7x=24-3
7x=21/:7
x=3
d) 7w=2w+5
7w-2w=5
5w=5/:5
w=1
e) 10z +5=5z+20
10z-5z=20-5
5z=15/5
z=3
f) 24u+7=20u=23
24u-20u=23-7
4u=16/:4
u=4
g) 9x+1=6x+2
9x-6x=2-1
3x=1/:3
x=0,33(3)
h) 15k+67=11k+8
15k-11k=8-67
4k= -59/4
k= -14,75

Proszę o najlepszą odpowiedź :)

2 5 2